Facile room temperature synthesis of ZnO nanoflower thin films grown at a solid-liquid interface - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Materials Science, 2014)
Hierarchical ZnO films consisting of nanoflower particulates are successfully grown by a solid-liquid interface reaction technique at room temperature without additives like surfactants, capping agent, or complexing agent. The structural, morphological, and photocatalytic properties of these films are studied using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and UV-Vis spectroscopy. The nucleation, growth processes and hence the resulting morphology of the end product can be regulated by changing the concentration of LiOH and the time of reaction. SEM throws light on the chronology of the flower formation by studying the intermediate morphology. Electron microscopy results indicated that these ZnO nanostructures self-assembled to produce flower-like nanostructures. The highest photocatalytic efficiency was observed for the films prepared at the concentration of LiOH 0.5 mg/mL in ethanol at 24 h. On the basis of the results, a plausible growth mechanism for the formation of flower-like ZnO nanostructures is discussed.